Use of successional sowing in evaluating cowpea (Vigna unguiculata) adaptation to drought in the Sudan savannah zone. 1. Seed yield response - Muleba, N.; Mwanke, M.; Drabo, I. (Cambridge University Press, 1991)
The results of this study indicated that this procedure is sufficiently sensitive to reflect the effects of tillage, residue cover and crusting on infiltration data. Raindrop impact reduced infiltration rates by crusting the soil surface. However, most of the management systems that left about 30% of residue cover protected the soil from raindrop impact as evidenced by the higher effective hydraulic conductivity. It is concluded that the model developed by Green and Ampt in 1911 satisfactorily fitted the infiltration data obtained from protected and crusted soil profiles. Also, residue cover and crusting greatly influenced the Green and Ampt infiltration parameter values